Rhizogenic behavior of black pepper cultivars to indole-3-butyric acid - Secundino, Welington; Alexandre, Rodrigo Sobreira; Schimildt, Edilson Romais; Schimildt, Omar; Magevski, Gizele Cristina; Martins, João Paulo Rodrigues (Acta scientiarum. Agronomy, 2014)
Little information is available regarding vegetative propagation of the species Piper nigrum L. to generate technical recommendations for the production of seedlings on a commercial scale. The purpose of this study was to investigate the rhizogenic behavior of cultivars of this species regarding indol-3-butyric acid (IBA). The experiment was performed at a vegetation house equipped with an intermittent nebulization irrigation system. The experimental site was located in the University Center of Northern Espírito Santo (CEUNES) of the Federal University of Espírito Santo (UFES), Brazil. The experimental design consisted of randomized blocks arranged in a 3 x 5 factorial scheme: three cultivars (Bragantina, Iaçará and Guajarina) x five IBA concentrations (0; 1,500; 3,000; 4,500 and 6,000 mg kg-1), with four repetitions of 16 cuttings each. Total immersion of the cuttings in IBA is recommended for the Iaçará and Guajarina cultivars, and immersion of only the basal region is recommended for cv. Bragantina. The recommended IBA concentration for these cultivars is 4,000 mg kg-1.